Discourses about race in the United States: A thematic analysis of short essays. (July 2021) - Raval, Vaishali V.; Ovia, Timothy; Freeman, McKenna; Raj, Stacey P.; Daga, Suchi S.
Highlights: Opinions about race range from color-blind ideology to racial equality. Some view race as divisive, whereas others consider race as providing community. Race may be salient aspect of identity for some but insignificant to others. The topic of race elicits contrasting emotions from pride to apprehension. Abstract: Conversations around race have come to the forefront of public discourses in the United States with incidents of police brutality leading to movements such as Black Lives Matter and its opposition, All Lives Matter. Although there is substantial psychological literature focusing on racial attitudes and intergroup relations, much of this research is experimental, failing to capture diverse and evolving viewpoints of people in the United States. In the present study, our aim was to understand folk definitions and diverse perspectives about the role of race in the United States in participants' own words. We thematically analyzed submissions to The Race Card Project ( n = 913), a publicly available platform, and responses from a sample of college students describing perspectives on race ( n = 1092). A total of 27 identified themes were organized in four domains: opinions about race, race-based interactions, race and identity, and emotions. Opinions about race ranged from color-blind ideology to racial equality, race as divisive or providing community, and excessive focus on race. References were made to historic and current race relations, assumptions based on skin color, prejudice and discrimination, White privilege, and "reverse racism." These findings contribute to evolving scholarly understanding of race in the United States, with implications for informing initiatives to promote race relations and reduce experiences of discrimination for individuals of color.